GROUND WATER QUALITY PROFILE OF KALA SHAH KAKU (Pakistan Journal of Science, 2025)
A study on the contamination of ground water by industrial effluent in different areas of Kala Shah Kaku has been conducted. Kala Shah Kaku is one of the industrial areas in Punjab. The industrial effluent is one of the major causes of drinking water contamination in such areas. Grounwater samples have been analyzed for their different characteristics. Standard laboratory techniques have been employed to determine various parameters from the samples. The mean values of pH, Na+, and SO42-are within the permissible limits of WHO standards. Whereas conductivity, turbidity, hardness, TDS, Cl-, Alkalinity, and potassium levels were above the permissible limit of WHO standard. On the basis of that we can say that the ground water of Kala Shah Kaku is hard and not suitable for drinking and it should be monitored.
Keywords: water; Kala Shah Kaku; hardness